Determination of the toxicity equivalency factors for ciguatoxins using human sodium channels. (February 2022) - Raposo-Garcia, Sandra; Louzao, M. Carmen; Fuwa, Haruhiko; Sasaki, Makoto; Vale, Carmen; Botana, Luis M.
Abstract: Ciguatoxins (CTXs) which are produced by dinoflagellates of the genus Gambierdiscus and Fukuyoa and share a ladder-shaped polyether structure, are causative compounds of one of the most frequent foodborne illness disease known as ciguatera fish poisoning (CFP). CFP was initially found in tropical and subtropical areas but nowadays the dinoflagellates producers of ciguatoxins had spread to European coasts. Therefore, this raises the need of establishing toxicity equivalency factors for the different compounds that can contribute to ciguatera fish poisoning, since biological methods have been replaced by analytical techniques. Thus, in this work, the effects of six compounds causative of ciguatera, on their main target, the human voltage-gated sodium channels have been analyzed for the first time. The results presented here led to the conclusion that the order of potency was CTX1B, CTX3B, CTX4A, gambierol, gambierone and MTX3. Furthermore, the data indicate that the activation voltage of sodium channels is more sensitive to detect ciguatoxins than their effect on the peak sodium current amplitude.